1986
DOI: 10.1523/jneurosci.06-09-02558.1986
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine stimulates glycogenolysis in mouse cerebral cortex: a possible coupling mechanism between neuronal activity and energy metabolism

Abstract: Adenosine promotes a concentration-dependent hydrolysis of 3H-glycogen newly synthesized from 3H-glucose by mouse cerebral cortical slices. The EC50 for this effect is 7 microM. Theophylline antagonizes the glycogenolysis induced by adenosine with an EC50 of 80 microM. The rank-order of potencies of adenosine agonists is adenosine 5'-cyclopropyl-carboxamide greater than 2-chloroadenosine much greater than N6-cyclohexyladenosine = adenosine, suggesting that adenosine promotes glycogenolysis via receptors of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(46 citation statements)
references
References 36 publications
2
43
0
1
Order By: Relevance
“…In fact, the activation of adenosine receptors can modify the primary metabolism of most cell types (see [1]) and this is also true for both neurons and astrocytes [101,102] and in particular for the control of glygogen metabolism [51, 103,104]. However, it still remains to be explored if this modulation of brain metabolism by adenosine receptors is implicated in the neuromodulatory or neuroprotective properties of adenosine or if it might be related with the trophic effects of purines (see [105]).…”
Section: Modulatory Roles Of Adenosinementioning
confidence: 99%
“…In fact, the activation of adenosine receptors can modify the primary metabolism of most cell types (see [1]) and this is also true for both neurons and astrocytes [101,102] and in particular for the control of glygogen metabolism [51, 103,104]. However, it still remains to be explored if this modulation of brain metabolism by adenosine receptors is implicated in the neuromodulatory or neuroprotective properties of adenosine or if it might be related with the trophic effects of purines (see [105]).…”
Section: Modulatory Roles Of Adenosinementioning
confidence: 99%
“…There are two additional cloned adenosine receptors, the A 2B and the A 3 receptors [12], but their roles have been less explored in the brain. Notably, A 2B R have been implicated in peripheral glucose homeostasis [15,16] and have been proposed to control astrocytic glycogen metabolism [17,18]. Furthermore, we recently observed that A 2B Rs control A 1 receptor (A 1 R)-mediated responses in hippocampal glutamatergic synapses [19].…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of brain glycogen can be further influenced by neurotransmitters (Magistretti et al, 1986;Pellerin and Magistretti, 1994) and anesthetics (Nelson et al, 1968;Nordstrom and Siesjo, 1978). Apparently, the degree of brain glycogen increase seems to be related to the depth, duration, and type of anesthesia used, with pentobarbital producing greater increases in glycogen content than, for example, ether (Nelson et al, 1968).…”
Section: Introductionmentioning
confidence: 99%